ANALISIS META: PENGARUH MODEL PEMBELAJARAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA - Heri Bastian; Syamsuri Syamsuri; Hepsi Nindiasari (LPPM Universitas Bina Bangsa, 2024)
This research aims to conduct a meta-analysis of the influence of learning models on students' conceptual understanding, with a focus on the crucial factor of effect size. The meta-analysis encompasses a review of various journals and empirical studies previously conducted in the field of education. Data collection methods include the selection of studies based on specific criteria and the extraction of relevant data, including information on the learning models used and their effect sizes. The analysis results indicate significant variations in the impact of learning models on students' conceptual understanding, with effect size being the determining parameter. Various learning models, such as cooperative learning, project-based learning, and student-centered learning methods, have been identified and analyzed to measure their impact on students' conceptual understanding skills. Furthermore, this meta-analysis provides insights into the relationship between effect size and learning contexts, including examples such as educational levels, subjects, and study durations. These findings can serve as guidelines for developing more effective learning strategies, especially in efforts to enhance students' conceptual understanding